INEL Evenki Corpus - Däbritz, Chris Lasse; Gusev, Valentin; Stoynova, Natalia (2024)
Corpus Citation Däbritz, Chris Lasse; Gusev, Valentin; Stoynova, Natalia. 2024. INEL Evenki Corpus. Version 2.0. Publication date 2024-12-31. Archived at Universität Hamburg. https://hdl.handle.net/11022/0000-0007-FE38-D. In: The INEL corpora of indigenous Northern Eurasian languages. https://hdl.handle.net/11022/0000-0007-F45A-1 Corpus Description The INEL Evenki Corpus has been created within the long-term INEL project (Grammatical Descriptions, Corpora and Language Technology for Indigenous Northern Eurasian Languages), 2016–2033. The corpus makes possible typologically aware corpus-based grammatical research on the Evenki (< Tungusic) language and expands the documentation of the lesser described indigenous languages of Northern Eurasia. The INEL Evenki Corpus covers Northern (Taimyr, Khantayskoe Ozero, Ilimpi, Yerbogachyon) and Southern (Sym, Barhahan, and to a smaller extent Stony Tunguska and Nepa) Evenki dialects. These are exactly the dialects which are or were in contact with other languages included in the INEL project, that is first and foremost Dolgan and Selkup. The INEL Evenki Corpus contains texts from different sources: Published texts from several text collections: Vasilevich (1936): the Ilimpi, Yerbogachyon, Sym, Nepa dialects; Anisimov (1936): the Stony Tunguska dialect; Brodskaya (1967): the Khantayskoe Ozero dialect. Transcripts of recordings obtained from the Taimyr House of National Arts (TDNT) in Dudinka (2000s) as well as transcripts of recordings made by and from Tat`yana V. Bolina, all of them representing the Khantayskoe Ozero dialect. For these texts, corresponding time-aligned audio files are available. Texts from the handwritten archive of the Russian ethnographer and linguist Konstantin M. Rychkov recorded in the 1900s/1910s, covering the Taimyr, Ilimpi, Sym, and Barhahan dialects. Each text in the corpus is provided with morphological glossing, translation into English, Russian, and German, as well as annotation of Russian borrowings. Some texts also have annotations for ...